THE MONOPOLY PRACTICE AND UNFAIR BUSINESS COMPETITION IN THE TECHNOLOGY TRANSFER ACTIVITY THROUGH THE FOREIGN PATENT IN INDONESIA - Rahmanisa Purnamasari Faujura; Elisatris Gultom; Sudjana Sudjana (UUM Journal of Legal Studies, 2021)
It is a common knowledge that technology development shall be in line with the development of a nation. This fact is raising the need of developing countries as Indonesia to maximize potential in the field of technology. However, it is not easy as it sounds, there are many obstacles for a country to develop its potential in technology, notably for the expert in the relevant country to master the necessary skills. Due to this limitation, many countries are beginning to fill-in the gap by registering license of foreign patent. It is expected that the use of foreign patent will replace the higher cost and longer time needed in developing local technology in the developing countries. Unfortunately, the use of foreign patent license does not itself automatically enhance one’s ability to master the necessary skills. Many cases where developing countries were deceived by the ‘grant-back’ clause attached to the foreign patent license. The licensee’s position is consequently considered has lower than of the licensor, which in its turn may rise monopoly practice and unfair business competition. This study is conducted with the purpose to formulate an effective technology transfer through the licensing of foreign patent that can refrain from the repetition of monopoly practice and unfair business competition, according to the TRIPs signed by WTO and the positive law in Indonesia. This study is using juridical-normative approach as the methodology of research, it also use analytical approach through the Law Number 13 of 2016 concerning Patent; Law Number 5 of 1999 concerning Prohibition of the Monopoly Practice and Unfair Business Competition as well as the Agreement on Trade-Related Aspects of Intellectual Property Rights signed by the World Trade Organization, with respect to the license agreement of the foreign patent. Based on the issue as established previously in this journal, the expected outcome of increased information dissemination towards countries using patent licensing agreement in technology and information development related to any matter in intellectual property specifically in licensing agreement, which has higher possibility for Monopolistic Practices and Unfair Business Competition. Therefore, shows that in principle in order to prevent the licensing of foreign patent to lead onto the monopoly practice and unfair business competition, a country must establish a controlling entity to supervise the execution of the foreign patent and at the same time, enacting harmonious rules and regulations with such supervision.